Study on CO2 gasification kinetics of biomass char based on pore structure analysis: Theoretical modelling of structural parameter ψ in random pore model. (22nd October 2020) - Song, Qianshi; Wang, Xiaohan; Gu, Chunhan; Li, Haowen; Huo, Jiepeng
Summary: In this work, the structural function of char gasification is modelled theoretically. Considering that different components will have different pore characteristics after pyrolysis, char is divided into different micro‐structures according to its corresponding components, and then a structural equation is constructed to realize the theoretical calculation of the structural parameter. Through comparison, it is found that the proposed model has high accuracy and shows applicability for different demineralized biomass samples. An analysis of the influence of sample characteristics on the structural parameter shows that, with an increase in char particle size and initial porosity, the structural parameter shows a decreasing trend, while, with an increase in fuel ratio, the structural parameter first increases and then decreases. The model can directly predict char gasification through the characteristic parameters of the sample, including proximate analysis, ultimate analysis, initial porosity of the sample and char particle size, thus replacing previous predictions of char gasification by testing the characteristic parameters of the char pores.